The Feasibility and Acceptability of Using Technology-Based Daily Diaries with HIV-Infected Young Men Who have Sex with Men: A Comparison of Internet and Voice Modalities. - Cherenack, Emily M; Wilson, Patrick A; Kreuzman, Andrew M; Price, Georgine N (AIDS and behavior, 2016)
This study delivered a daily diary to 67 HIV-infected men who have sex with men (MSM) between 16 and 24 years old for 66 days to measure HIV-risk behaviors and other psychosocial variables via two diary modalities: internet (accessible via any web-enabled device) and voice (accessible via telephone). Participants were randomized to complete one diary modality for 33 days before switching to the second modality for 33 days. The study was implemented in three urban HIV health care centers in the United States where participants were receiving services. Through diary data and qualitative interview data, we examined the feasibility and acceptability of the dairies and identified barriers and facilitators of dairy compliance. Results show high participant retention in the daily diary (93.4 %) and high compliance for the number of dairies completed (72.4 %). Internet diaries were preferred by 92 % of participants and completed at a significantly higher rate (77.5 %) than voice diaries (67.7 %). Facilitators included opportunities for self-reflection and cathartic sharing, monetary compensation, relationships with study staff, and daily reminders. Barriers included being busy or not having privacy at the time of reminders, forgetting, and falling asleep. Participants also described barriers and facilitators unique to each modality. Overall, both modalities were feasible and acceptable for use with our sample of HIV-infected MSM.